Expression of Francisella pathogenicity island protein intracellular growth locus E (IglE) in mammalian cells is involved in intracellular trafficking, possibly through microtubule organizing center. Issue 4 (5th July 2018) - Shimizu, Takashi; Otonari, Shiho; Suzuki, Jin; Uda, Akihiko; Watanabe, Kenta; Watarai, Masahisa
Abstract: Francisella tularensis is the causative agent of the infectious disease tularemia and is designated a category A bioterrorism agent. The type VI secretion system encoded by the Francisella pathogenicity island (FPI) is necessary for intracellular growth; however, the functions of FPI proteins are largely unknown. In this study, we found that the FPI protein intracellular growth locus E (IglE) showed a unique localization pattern compared to other FPI proteins. Deleting iglE from Francisella tularensis subsp. novicida ( F. novicida ) decreased intracellular growth. Immunoprecipitation and pull‐down assays revealed that IglE was associated with β‐tubulin. Additionally, GFP‐fused IglE colocalized with microtubule organizing centers (MTOCs) in 293T cells. The iglE deletion mutant was transferred with dynein toward MTOCs and packed into lysosome‐localizing areas. Conversely, the wild‐type F. novicida exhibited intracellular growth distant from MTOCs. In addition, IglE expressed in 293T cells colocalized with dynein. These results suggest that IglE helps to prevent dynein‐ and MTOC‐mediated intracellular trafficking in host cells to inhibit the transport of F. novicida toward lysosomes. Abstract : In this study, we found that one of virulence proteins intracellular growth locus E (IglE) was necessary for intracellular growth of F.  tularensis subsp. novicida, IglE was associated with β‐tubulin and microtubule organizing center (MTOC), IglE disturbed bacterial trafficking of host cells. These results suggested that IglE performed an essential role in inhibiting the fusion of Francisella‐containing membrane compartment with lysosome by preventing MTOC‐mediated membrane trafficking pathway.